2017
DOI: 10.5604/01.3001.0010.4889
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Human Enteroviruses Associated with Hand, Foot and Mouth Diseases in Poland, 2013–2016

Abstract: A b s t r a c tThe objective of the present study was to describe the molecular characteristics of enteroviruses associated with hand, food, and mouth disease (HFMD) in Poland. Clinical material from HFMD cases, that occurred during 2013-2016 were examined. It has been showed that coxsackievirus A6 (CVA6), CVA10 and CVA16 were circulating in the country. Phylogenetic analysis showed that Polish CVA6 strains were divided into two distinct clusters suggesting two independent introductions. This is the first repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Co-circulation of CV-A6 with CV-A10 and CV-A16 was already reported previously [7,39] and in a study of HFMD cases in Poland between 2013-2016 the emergence and cocirculation of CV-A6 with CV-A10 and CV-A16 was also confirmed [9]. In our study CV-A6, CV-A16 and EV-71 were the only three types identified in specimens associated with HFMD, however only CV-A6 was detected in any HFMD samples since 2013.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Co-circulation of CV-A6 with CV-A10 and CV-A16 was already reported previously [7,39] and in a study of HFMD cases in Poland between 2013-2016 the emergence and cocirculation of CV-A6 with CV-A10 and CV-A16 was also confirmed [9]. In our study CV-A6, CV-A16 and EV-71 were the only three types identified in specimens associated with HFMD, however only CV-A6 was detected in any HFMD samples since 2013.…”
Section: Discussionsupporting
confidence: 79%
“…A change in the clinical phenotype of CV-A6 became evident when a large outbreak of HFMD caused by CV-A6 in Finland in 2008 was reported [6]. This was followed by several reports of CV-A6 associated HFMD from Europe [7][8][9], North America [10,11] and Asia [12][13][14][15]. In the last decade CV-A10 was also reportedly an agent of HFMD [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…6-10 CV-A6 and CV-A10 are the most common serotypes for mild HFMD worldwide and in China since 2010. 11-18 We found that the number of HFMD cases has increased since the nationwide HFMD outbreak in China in 2008; HFMD has been the leading cause of significant mortality in China since 2013 to present, according to the report of National Health Commission of the People’s Republic of China.…”
Section: Introductionmentioning
confidence: 96%
“…Coxsackievirus A6 (CV-A6) and coxsackievirus A10 (CV-A10) are the most common serotypes for mild HFMD worldwide and in China since 2010 [11][12][13][14][15][16][17][18]. We found that the number of HFMD cases has increased very much since the nationwide HFMD outbreak in China in 2008, and the number of HFMD cases has been the head of the lethal infectious diseases in our country for five consecutive years since 2013, according to the report of National Health Commission of the People's Republic of China.…”
Section: Introductionmentioning
confidence: 99%
“…Coxsackievirus A6 (CV-A6) and coxsackievirus A10 (CV-A10) are the most common serotypes for mild HFMD worldwide and in China since 2010 [11][12][13][14][15][16][17][18]. We found that the number of HFMD cases has increased very much since the nationwide HFMD outbreak in China in 2008, and the number of HFMD cases has been the head of the lethal infectious diseases in our country for five consecutive years since 2013, according to the report of National Health Commission of the People's Republic of China.…”
Section: Introductionmentioning
confidence: 99%